The Effect Payment Methods and Services on The Satisfaction BPJS Health Members South Tangerang - Sopiyana, Muhammad (Universitas Pamulang, 2020)
As a form of good service is to see how important the implementation of good service standards in a government administration and to see if the form of public service has been in accordance with government policy which in this case is bpjs health office, especially with regard to health welfare services for the People of Indonesia especially in South Tangerang, in its implementation is still not maximal, namely by looking at some things related to the effectiveness of the community namely by looking at how the apparatus or implementing officers in serving the community , how are the regulations on the method of payment of mandatory dues of BPJS Health members, how bpjs kesehatan network activities are carried out in South Tangerang, and how the public can enjoy the service so that the community is satisfied by BPJS Health services in South Tangerang The research method is a quantitative method that emphasizes the aspect of measurement objectively towards social phenomena that are the people of BPJS health services in South Tangerang. The data collection method uses primary data. Tekning sampling used is a conviniens sample technique with respondents who are members of BPJS south tangerang city. The analysis used in this study is a multiple linear regression analysis that is with the calculation of spss through validity testing, reality testing, classic assumption testing, and multiple linear regression analysis. The results of this research show that (1) Payment methods have a positive effect on the satisfaction of members of BPJS Health, (2) BPJS Health services positively affect the satisfaction of BPJS Health members, (3) Payment methods and services BPJS Shared health the same affects the satisfaction of BPJS healthcare members.